Designing and Implementing a System for Tracking Functional Status After Stroke: A Feasibility Study. Issue 6 (14th November 2012) - Sandel, M. Elizabeth; Jette, Alan M.; Appelman, Jed; Terdiman, Joseph; TeSelle, Marian; Delmonico, Richard L.; Wang, Hua; Camicia, Michelle; Rasch, Elizabeth K.; Brandt, Diane E.; Chan, Leighton
Abstract : Objective: To determine the feasibility of tracking stroke patients' functional outcomes in an integrated health system across a care continuum using the computer version of the Activity Measure of Post‐Acute Care (AM‐PAC). Setting: A large integrated health care system in northern California. Participants: A total of 222 stroke patients (aged ≥18 years) who were hospitalized after an acute cerebrovascular accident. Methods: An AM‐PAC assessment was made at discharge from sites of care, including acute hospital, inpatient rehabilitation hospital, skilled nursing facility, home during home care, and outpatient settings. Assessments also were completed in the patient's home at 6 months. Data from the AM‐PAC program were integrated with the health care system's databases. Main Outcome Measurements: (1) AM‐PAC administration time at the various sites of care; (2) assessment of a floor or a ceiling effect; and (3) administrative burden of tracking participants. Results: AM‐PAC assessment sessions averaged 7.9 minutes for data acquisition in 3 domains: Basic Mobility, Activities of Daily Living, and Applied Cognition. Participants answered, on average, 27 AM‐PAC questions per session. A small ceiling effect was observed at 6 months, and there was a larger ceiling effect when the instrument was administered in an institution, ie, when the AM‐PAC institutional item bank was used rather than the community item bank. It was feasible to track patients and to assess their function using the AM‐PAC instrument from institutional to community settings. Implementation of the AM‐PAC in clinical environments, and the success of the project, were influenced by instrumental, technological, operational, resource, and cultural factors. Conclusions: This study demonstrates the feasibility of implementing a single functional outcome instrument in clinical and community settings to measure rehabilitation functional outcomes of stroke patients. Integrating the AM‐PAC measurement system into clinical workflows and the electronic medical record could provide assistance to clinicians for medical decision making, functional prognostication, and discharge planning.